Self and Peer Correction to Improve College Students’ Writing Skills (2018)
This paper describes college students’ writing development process during their foreign language classes throughout a semester. Self and peer correction were implemented to promote error awareness along with the use of an error code and error log in a fifth semester class. The results show that both strategies benefited students’ writing skills and self-awareness which in turn produced, among other outcomes, the development of critical self-assessment of their writing and responsibility for their own learning. This study highlights the importance of allocating class time for continuous training to allow students to systematize their writing practices.